The Relationship between Self-esteem and Student Lifestyle - Kamil Pardomuan Hts; Indah Sukmawati (Universitas Negeri Padang, 2021)
Many adolescents cannot control their lifestyle, one of which is due to low self-esteem, so they have a negative lifestyle.This study aims to see how the correlation between self-esteem and lifestyle among students of MA N 1 Kerinci. This research is a descriptive correlational study, with a sample of 176 students. This study used an instrument in the form of a CFSEI-2 (The Culture Free Self Esteem Inventory) inventory for self-esteem variables and a questionnaire that was compiled using a Likert scale model for lifestyle variables.The results of this study indicate that (1) students of MA N 1 Kerinci have self-esteem which is in the very low category with a percentage of 35.80%;(2) while in terms of lifestyle, it is in the quite good category with a percentage of 40.91%;(3) the results of the correlation analysis showed that a significant value showed a number of 0.089 which was greater than 0.05, meaning that there was no correlation between self-esteem and the lifestyle of students of MA N 1 Kerinci.